Instructional materials management in literature to en hance students’ literacy competence in elementary school settings - Ratih Cahyani; Ricky Yoseptry (At Turots: Jurnal Pendidikan Islam, 2025)
This research is motivated by the concept of literacy competence, which encompasses the ability to read, write, comprehend, and interpret information critically. Literacy competence is not merely limited to the technical skills of reading and writing but also includes critical thinking, contextual understanding, and the capacity to relate information to personal experiences and broader knowledge. This study employs a qualitative approach with a descriptive-analytic method. The research was conducted in Sumedang Regency, specifically at two selected elementary schools: Malangbong Public Elementary School and Arrafi Elementary School. The findings of this study can be summarized as follows: (a) The planning stage involves determining the objectives of literary instructional material management; (b) The organizing stage is carried out by forming a working group consisting of the principal, vice principal, and teachers to create a management team for literary instructional materials; (c) The implementation stage relates to activities in managing literary instructional materials in collaboration with the school literacy program, with the expected outcome of fostering and developing a literacy culture within the elementary school environment; (d) The evaluation and follow-up stage begins with analyzing the school’s education report to assess literacy performance and identify emerging challenges. Although reading provides numerous benefits, not all students are interested in, aware of, or willing to cultivate a strong reading culture.